A sagrada autoridade em El Señor Presidente, de Miguel Ángel Asturias - Lara Fagundes Pereira (2024)
This work seeks to reflect on the aspects of the myth found in the novel El Señor Presidente, by Miguel Ángel Asturias (1899-1974). Among these aspects we highlight those that, in this context, act directly in the suspension of a common and linear logic of the world conception: the time, the space, the rite, the interruptions caused by oneiric or unconscious phenomena and, finally, the figure of the President himself, which is where all the mythical force of the work in question converges. To think about the myth, we will rely, in particular, on the studies of Mircea Eliade (1969, 1972, 1992), as well as the theory of Simões Jorge (1994) and Roger Caillois (1979). In relation to readings of the novel, we will draw on names such as Selena Millares (2000), John Kraniauskas (2000), Jorge Caro (1999), Lucrecia Penedo (2020), Alaide Foppa (1971), Jean-Marie Saint-Lu (2000 ) and Gerald Martin (2000), the latter being the organizer of the critical edition used in this analysis. We seek to understand how these mythical forces operate within the narrative, that is, through which elements it is possible to make such statements, as well as thinking about how the relationship between the myth and the authority expressed therein works.